Correlation Between Number of Retrieved Oocytes and Pregnancy Rate After In Vitro Fertilization/IntraCytoplasmic Sperm Infection - Tanya Timeva; Tanya Milachich; Irena Antonova; Tanya Arabaji; Atanas Shterev; Hatim A. Omar (The Scientific World Journal)
The implementation of safe and maximally effective ovarian stimulation is a major aim for in vitro fertilization (IVF) teams. The goal of controlled ovarian hyperstimulation (COH) is to supply enough oocytes with normal maturation to insure the consequent biological procedures. A variety of different stimulation protocols have been suggested and an individual selection of the correct stimulation protocol is mandatory. The aim of the present study is to evaluate the correlation between number of retrieved oocytes and clinical pregnancy rate (CPR) after IVF or intracytoplasmic sperm injection (ICSI) procedures. We reviewed 1017 cycles in a total of 975 patients. The study results clearly demonstrate that the aspiration of less than 5 oocytes significantly reduced pregnancy rate. The aspiration of a large number of oocytes (>15) does not lead to an increase of the treatment effect and, at the same time, increases the risk of ovarian hyperstimulation syndrome. The major goal is to obtain 5—15 oocytes as a “gold standard”, connected to optimal pregnancy rate after assisted reproduction (ART).